Activity monitor and management system using Bluetooth Low Energy (BLE) - Roxas, Abby Maurea Imus (Nanyang Technological University, 2021)
Contact tracing has been considered a critical strategy and a necessity to combat and contain the CoronaVirus-19 (Covid-19) outbreak. Contact tracing involves identifying, assessing, managing people who have been exposed to people who are infected with Covid-19. Speed in identifying is of crucial importance in identifying the contacts of an infected person, so they can isolate and prevent further spread of the virus. However, manual contact tracing is time-consuming and incomplete due to imperfect recollection of close contacts which may lead to delayed isolation and thus, further spread of the virus. Therefore, the use of digital contact tracing application was a common international response deployed to assist in containing Covid-19 outbreak. This project aims to develop another approach to a digital contact tracing solution that differs from the protocols and design implemented in TraceTogether. An Android mobile application named COVInform.me is developed with decentralization in mind, from the generation of temporary IDs to exposure checks. COVInform.me is developed on Android development environment using Android Studio and written in Java. Firebase services are used to support back-end of the application.